1986
DOI: 10.1002/bies.950050403
|View full text |Cite
|
Sign up to set email alerts
|

Cell migrations during morphogenesis: Some clues from the slug of Dictyostelium discoideum

Abstract: Starvation induces free‐living Dictyostelium discoideum amoebae to form slugs that typically contain 100,000 cells. Only recently have sufficient clues become available to suggest how coordinated cell actions might result in slug movement. We propose a “squeeze‐pull” model that involves circumferential cells squeezing forward a cellular core, followed by pulling up of the rear. This model takes into account the different classes of cells in the slug; it is proposed that prestalk cells are engines and prespore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…We also showed that the observed collective coordinated motion of cells in Dictyostelium, from aggregation to slug movements, follows directly from the behavior of individual cells; no additional assumptions are necessary, such as the squeeze-pull mechanism [49] for the slug. Also since we balance all the forces, the model allows us to study the differences in movements when the cells are dragging themselves forward by grabbing onto other cells and not propelling themselves forward by some internal "jet engine" [45].…”
Section: Discussionmentioning
confidence: 73%
“…We also showed that the observed collective coordinated motion of cells in Dictyostelium, from aggregation to slug movements, follows directly from the behavior of individual cells; no additional assumptions are necessary, such as the squeeze-pull mechanism [49] for the slug. Also since we balance all the forces, the model allows us to study the differences in movements when the cells are dragging themselves forward by grabbing onto other cells and not propelling themselves forward by some internal "jet engine" [45].…”
Section: Discussionmentioning
confidence: 73%
“…We have shown that the observed collective, coordinated motion of cells in Dd, from aggregation to slug movements, follows directly from the behavior of individual cells; no additional assumptions or mechanisms, such as the squeeze-pull mechanism (49), are necessary to produce motion of an aggregate. We are able to simulate large numbers of interacting cells, accounting for both the passive interactions caused by adhesion and the active locomotory forces, and we allow a restricted class of deformations of individual cells.…”
Section: Discussionmentioning
confidence: 91%
“…Our results indicate that all cells in the prespore zone move forward at similar speed, while cells in the tip rotate around the slug axis. The squeeze-pull model (16) postulates that the cells in the slug move forward by contraction of a ring of cells in the back of the slug and pulling of cells which are stationary to the substratum in the front of the slug. We never observed stationary cells in the anterior part of the slug as claimed by the squeeze-pull model.…”
Section: Resultsmentioning
confidence: 99%